(untitled) (Journal of Computational Mathematics, 2021)
We discuss the Hermite-type collocation method for the solution of Volterra integral equation with weakly singular kernel. The constructed approximation is a cubic spline in the continuity class C^1. We prove that this method is convergent with order of four.